Redefining the battle against colorectal cancer: a comprehensive review of emerging immunotherapies and their clinical efficacy - Shebbo, Salima; Binothman, Najat; Darwaish, Manar; Niaz, Hanan A.; Abdulal, Rwaa H.; Borjac, Jamilah; Hashem, Anwar M.; Mahmoud, Ahmad Bakur (Frontiers in Immunology, 2024)
Colorectal cancer (CRC) is the third most common cancer globally and presents a significant challenge owing to its high mortality rate and the limitations of traditional treatment options such as surgery, radiotherapy, and chemotherapy. While these treatments are foundational, they are often poorly effective owing to tumor resistance. Immunotherapy is a groundbreaking alternative that has recently emerged and offers new hope for success by exploiting the body's own immune system. This article aims to provide an extensive review of clinical trials evaluating the efficacy of various immunotherapies, including CRC vaccines, chimeric antigen receptor T-cell therapies, and immune checkpoint inhibitors. We also discuss combining CRC vaccines with monoclonal antibodies, delve into preclinical studies of novel cancer vaccines, and assess the impact of these treatment methods on patient outcomes. This review seeks to provide a deeper understanding of the current state of CRC treatment by evaluating innovative treatments and their potential to redefine the prognosis of patients with CRC.